Effect of Physics Education Technology (PhET) Simulations: Evidence from STEM Students’ Performance - Yunzal, Jr., Ananias N; Casinillo, Leomarich F (LPPM Undiksha, 2020)
This study aimed to find out if Physics Education Technology (PhET) simulations can improve the performance of the Baybay City Senior High School STEM students on the selected topic in physics, that is, electrodynamics. This study utilized a quasi-experimental type where pre-test and post-test are multiple choice type of test and involved 72 STEM students. The grouping of the students was identified based on their sections, one section served as the control group and other is the experimental group. Experimental group is allowed to play the PhET simulation for an hour utilizing their vacant period every day, while the control is not exposed to any activity that intervene leading to the creation of formal construct of ideas in electrodynamics. Result showed that mean scores of the control and experimental groups does not imply a significant difference, despite of the interest shown by the students in playing the said simulation. Perhaps, students are more attracted to simulation in which they have gone through during their lectures. Furthermore, study shows that the performance of students before and after exposure to PhET simulation does not necessarily pose a big difference but indicates a slight improvement to their performances.